Scattered-radiation field of a small betatron in nondestructive testing under nonstationary conditions; Soviet Journal of Nondestructive Testing; Vol. 20, iss. 2 - Bespalov V. I.; Lunev V. I.; Sedoi A. G.; Chakhlov V. L. Vladimir Lukianovich; Shtein M. M. Mikhail Mikhailovich (1984, 1984)
The SR (scattered radiation) fields of MIB-4 and TB-15 portable betatrons were examined by experiment and numerical calculation. The absorbed dose in air directly adjoining the outer wall of the instrument were determined in both cases. It is concluded that the radiation dose to equipment or man can be reduced by a substantial factor by appropriate choice of position near the betatron. The constraints on dose rate for man are known (not more than 2. 13 multiplied by 10** minus **1**0 A/kg, and the same for equipment (not more than 1. 28 multiplied by 10** minus **7 A/kg), which enables one to determine the permissible exposure times in the SR field with or without additional shielding.